1994
DOI: 10.1021/j100065a046
|View full text |Cite
|
Sign up to set email alerts
|

Motions of Trimethylphosphine on the Surface of Acid Catalysts

Abstract: On acid surfaces, trimethylphosphine (TMP) forms either Brbnsted or Lewis site adducts, TMPH+ or TMP:L, respectively. In TMPH+, the 31P magnetization decay is practically monoexponential and the 31P spin-lattice relaxation rate (1/T1) is not thermally activated. In TMP:L, the magnetization decay is biexponential and the relaxation rate is thermally activated. Using the known internuclear distances in TMPH or TMPH+, it is shown that the relaxation rates can be accounted for by using the homo-and heteronuclear (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 10 publications
1
23
0
Order By: Relevance
“…Many authors observed the formation of Lewis acid site after dealumination of zeolites [10][11][12][13][14][15][16], but different opinions on the origin of Lewis acid site were reported in the literature. In general, there are two typical models.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many authors observed the formation of Lewis acid site after dealumination of zeolites [10][11][12][13][14][15][16], but different opinions on the origin of Lewis acid site were reported in the literature. In general, there are two typical models.…”
Section: Discussionmentioning
confidence: 99%
“…However, the limitation of this technique lies in the difficulty to determine the strength of the acidity and the number of acid sites in a quantitative way for the different extinction coefficients of each adsorbed species. Trimethylphosphine has emerged as a promising approach to characterize the acid sites in zeolites [10][11][12] and other materials [13][14][15] using 31 P MAS NMR spectroscopy. Trimethylphosphine (TMP) is suitable for 31 P MAS NMR studies as it has isotope of 100% natural abundance, nuclear spin of 1/2, and large gyromagnetic ratio.…”
Section: Introductionmentioning
confidence: 99%
“…The reason may be that the TMPO is always adsorbed on the defects of the nanotubes, where the large conjugated system is broken. Furthermore, unlike the biexponential 31 P spinlattice relaxation behavior of TMP adsorbed on Lewis acid sites in zeolites, [28] the spin-lattice relaxation behaviors are monoexponential for TMPO in CNTs. Figure 3b shows a representative simulation of the relaxation curve from Figure 3a, which could be well fitted with the monoexponential function: [29] Figure 4b shows the variation of 31 P spin-lattice relaxation rate versus the inverse of the absolute temperature for TMPO in o-CNT.…”
Section: Resultsmentioning
confidence: 86%
“…Fourth, it has been found that CSA to the relaxation rate of adsorbed TMP is negligible even with CSA as large as 200 kHz. [28] Hence, the main relaxation contribution for 31 P nucleus is from the nine methyl protons in TMPO molecule. Spin-lattice relaxation rate dominated by proton dipolar interactions, and the modulation of these interactions by molecular motions, have been studied thoroughly.…”
Section: Resultsmentioning
confidence: 99%
“…The 31 P nucleus is an attractive candidate for surface acidity characterization studies as it possesses a large chemical shift range and it is, from an NMR point of view, a sensitive nucleus (100% natural abundance). Among the possible phosphored bases, TMP has been employed to probe brönsted and Lewis acidity in zeolites [10][11][12][13] and other materials [14][15][16][17][18]. because of its high basic strength (TMP basicity is about 1000 times greater than that of pyridine) and its rather small size, this probe is able to be adsorbed on a large amount of the solid acid sites.…”
Section: Preparation Of Chlorinated G-aluminasmentioning
confidence: 99%